Ammonia-storage in lithium intercalated fullerides. Issue 42 (25th September 2015) - Pontiroli, D.; D'Alessio, D.; Gaboardi, M.; Magnani, G.; Milanese, C.; Duyker, S. G.; Peterson, V. K.; Sharma, N.; Riccò, M.
Abstract : Li6 C60 can absorb up to 14 NH3 per C60 ; its structural evolution upon desorption is studied by neutron powder diffraction. Abstract : Ammonia has been proposed as an indirect hydrogen carrier, as solid-state ammonia-storage could be easier than directly absorbing hydrogen in materials. Here we investigate the structural evolution of hyper-ammoniated lithium fullerides (ND3 ) y Li6 C60 during ammonia desorption, using in-situ high intensity neutron powder diffraction. In (ND3 ) y Li6 C60, ammonia molecules are stored in their neutral state inside the inter-fullerene interstices and are coordinated to the intercalated Li ions, forming Li–ND3 clusters. Li6 C60 is found to absorb up to 36.8 wt% ND3, which corresponds to approximately 14 ammonia molecules per C60 . The ammonia release, studied either in-situ or ex-situ by means of manometric analyses and differential scanning calorimetry, takes place in two main steps, at 350–410 K and 500–540 K, respectively. This corresponds to two clear 1 st order structural phase transitions and the absorption process is partially reversible. These findings suggest that the system could be a good candidate for ammonia-storage applications.